Corporate Social Responsibility Disclosure Dimensions and Financial Performance: A Study of Selected Listed Banks, Finance and Insurance Companies in Sri Lanka - Niresh, J.A.; Silva, W.H.E. (My University, 2020)
In recent years, the level of enthusiasm on the part of academics and managers in issues related with Corporate Social Responsibility (CSR) has developed impressively to the point that CSR is considered a significant element capable of influencing the achievement of a deliberate strategy. The study is expected to find out the relationship between the dimensions of Corporate Social Responsibility Disclosure (CSRD) and future Financial Performance. For the purpose of the study, data is gathered from thirty-three companies and for the selection of sample, purposive sampling method is used. Data in connection to predictors is gathered from 2010 to 2014 and data in connection to outcome variables is collected from 2011 to 2015. In terms of the dimensions of CSR, individually they are not noteworthy with the exception of Educational CSR and Financial Performance; Environmental CSR and ROE; and Employee CSR and ROA, the findings uncover.
Keywords: CSRD; ROE; ROA; CSR